Meta‐analysis of Meniett Therapy for Ménière's Disease. (23rd August 2013) - Ahsan, Syed F.; Standring, Robert T.
Abstract : Objectives: Evaluate the efficacy of Meniett micropressure treatment for Ménière's disease by performing a meta‐analysis of all relevant treatment studies. Methods: Systematic review of the English literature using Medline, Ovid, and Cochrane library from January 1996 to December 2012. We selected all studies for which the Meniett micropressure device was used to treat patients with definitive unilateral Ménière's disease. We did not include isolated case reports and general reviews. Random and fixed models were used to estimate overall effect size. Results: Of 80 abstracts screened for relevancy, 18 studies were selected for further review. For hearing, only 9 studies reported pure tone average (PTA) pre‐ and post‐Meniett application. The difference in PTA between pre‐ and post‐micropressure device application was not significant ( P = 0.72). Seven studies reported American Academy of Otolaryngology (AAO) functional score pre‐ and post‐treatment. Analysis shows significant improvement of AAO functional score after treatment ( P = 0.04). Eight studies reported frequency of vertigo before and after treatment. The treatment was found to be significant in reducing frequency of vertigo ( P < 0.0001). Conclusions: The Meniett device appears to be a safe, non‐destructive treatment alternative for patients refractory to initial medical therapy for Ménière's disease. The overall body of literature on the efficacy of the Meniett device is sparse and is an obvious limitation of this analysis, yet the data obtained will help to enlighten practitioners on the usefulness of the Meniett device.